2020
DOI: 10.1038/s41598-020-60721-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and genetic diversity of adeno-associated viruses in bats from coastal areas of Southeast China

Abstract: Bats are associated with several important zoonotic viruses from different families. One example includes adeno-associated viruses (AAVs), that are extensively detected in several animals, especially primates. To understand AAVs distribution and genetic diversity in the coastal areas of Southeast China, a total of 415 intestine samples were mostly collected from two provinces of southeast China, i.e., Zhejiang and Fujian province. Intestine samples from five bat species were collected for AAVs detection. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Cao et al suggested that there may be shorter isoforms that are suffixes of the above sequence starting from one of the other two methionines among the first 50 amino acids [ 22 ]. A search of the protein non-redundant (nr) database with X protein as query found only one significant match (E-value 0.0002 to sequence QDX47270.1, which is the 760aa capsid protein of another AAV found in the Chinese bat species Rhinolophus pusillus [ 36 ]. Interestingly a BLASTP search [ 29 ] with QDX47270.1 as query finds many capsid proteins from AAV sequences aligning within the interval [1.435] of QDX47270.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al suggested that there may be shorter isoforms that are suffixes of the above sequence starting from one of the other two methionines among the first 50 amino acids [ 22 ]. A search of the protein non-redundant (nr) database with X protein as query found only one significant match (E-value 0.0002 to sequence QDX47270.1, which is the 760aa capsid protein of another AAV found in the Chinese bat species Rhinolophus pusillus [ 36 ]. Interestingly a BLASTP search [ 29 ] with QDX47270.1 as query finds many capsid proteins from AAV sequences aligning within the interval [1.435] of QDX47270.…”
Section: Resultsmentioning
confidence: 99%
“…
Fig. 1 Visualization of the adeno-associated virus strain 2 (AAV2) genome including the X gene [ 20 ] and a promoter-enhancer region [ 36 ] that may be important to carcinogenesis but are not typically shown in schematic illustrations of AAV2
…”
Section: Introductionmentioning
confidence: 99%
“…Bat adeno-associated virus (BtAAV, Chiropteran dependoparvovirus 1 ) was identified in fecal swabs of 19 bat species in five Chinese provinces in 2007–2008 [ 219 ]. Intestinal samples from 5 species of bats in Southeast China showed that 18.6% were positive for AAVs, suggesting a wide distribution of these viruses [ 220 ]. Analysis of the BtAAV capsid structure using sequence analysis and cryo-EM revealed unique structural differences to human AAVs, including insertions and deletions in the capsid surface loops [ 221 ].…”
Section: Genus Dependoparvovirusmentioning
confidence: 99%
“…Bats are a rich source of AAV genetic diversity [ 68 , 69 ] and may provide capsids with improved tropism and immune evasion properties. For example, bat AAV sequences have low capsid sequence identity (<60%), reduced antibody neutralization profiles, and increased muscle to liver transduction ratios compared to primate AAVs [ 70 ].…”
Section: Aav Capsid Modification Strategiesmentioning
confidence: 99%